2023
DOI: 10.3390/brainsci13050713
|View full text |Cite
|
Sign up to set email alerts
|

The Olfactory Bulb in Companion Animals—Anatomy, Physiology, and Clinical Importance

Abstract: The Olfactory Bulb is a component of the Olfactory System, in which it plays an essential role as an interface between the peripheral components and the cerebral cortex responsible for olfactory interpretation and discrimination. It is in this element that the first selective integration of olfactory stimuli occurs through a complex cell interaction that forwards the received olfactory information to higher cortical centers. Considering its position in the organizational hierarchy of the olfactory system, it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…As the olfactory bulb has extensive direct or indirect connections with different brain regions, activating the olfactory epithelium and subsequent activation of the olfactory bulb can influence activity in various brain regions [69]. In a seminal study, Grosmaitre et al (2007) demonstrated that sensory neurons in the mammalian olfactory epithelium exhibit mechanosensitivity [22].…”
Section: Discussionmentioning
confidence: 99%
“…As the olfactory bulb has extensive direct or indirect connections with different brain regions, activating the olfactory epithelium and subsequent activation of the olfactory bulb can influence activity in various brain regions [69]. In a seminal study, Grosmaitre et al (2007) demonstrated that sensory neurons in the mammalian olfactory epithelium exhibit mechanosensitivity [22].…”
Section: Discussionmentioning
confidence: 99%